(untitled) (Indian Journal of Animal Production and Management, 2015)
A field study was conducted to collect the information on housing and feeding management practices followed by the dairy animal owners of Navsari district of South Gujarat. All dairy animal owners (both rural and urban area) provided same kind of housing to their dairy animals. About 72.33 per cent respondents kept their animals in close house. Around 73.33 per cent of the respondents provided manger to their animals of which 50.33 per cent of the respondents had pucca type of manger while 23 per cent of the respondents had wooden manger. Majority of the respondents (58%) followed stall feeding for their dairy animals. About 65.32 per cent of the dairy farmers grew fodder. Paddy straw was major ingredient (82%) used as dry fodder. About 54 percent of farmers fed homemade + compounded cattle feed as concentrates to their milking animals, based on milk production, mainly after milking (43%).